Fotografia e interação: modos de apresentação do adolescente e da escola no ciberespaço - Zanin, Larissa Fabricio (2012)
Information technology has cleared the way for sharing images and information providing new forms of sociability through digital social networks. Within this context, this work proposes to understand the meanings of photographs of teenagers in Orkut albums and the ways that the school is presented by adolescents on these albums and digital social network itself, considering this albums on Orkut as carriers of meanings that presents from those articulations, in languages that syncretized form, verbal and visual. It presents as theoretical studies relating to discourse analysis that permeate the discourse and Semiotics studies about the scheme proposed by Eric Landowski visibility, among other relevants considerations to sociossemiótica. It also addresses questions about the power of the photographic image and the character of veridiction, beyond the issues inherent at the construction of identity / alterity through social practices experienced in cyberspace